Microscopic modeling on tribological behaviors of seal composites for aiding the selection of sealing material in a wet clutch. (February 2019) - Gong, Ran; Zhai, Xinze; Che, Huajun; Zhu, Maotao; Wang, Heng
A numerical method is proposed to investigate the tribological behaviors of three sealing composite materials based on the movable cellular automata (MCA). The MCA method is a discrete approach that treats a simulated medium like an ensemble of interacting cellular automata. These sealing materials are applied to the seals that are assembled in the wet clutch of an automobile. Polytetrafluoroethylene (PTFE) matrix materials with different proportions of the same filler materials are chosen as samples in this study. Based on the discretization concept, this study visualizes the microscopic dynamic responses, formation and evolution of the frictional layer of sealing material surfaces, by considering properties of filler materials and material inhomogeneity in the composites of the seals. The changing processes of friction coefficients and worn automata are obtained within the simulation time. PTFE composites with sealing ring configurations are tested in the test rig. Scanning electron microscopy is utilized to examine composite microstructures, and the results indicate that microstructure wear mechanisms are consistent with MCA simulations. The nature of filler material is investigated and the wear patterns of PTFE materials are revealed through the MCA method, which provides an option for sealing material selection and will improve the efficiency of the sealing design in the wet clutch.